New approaches & phenomenons in inmigration studies: religious movements in the hearth of the United States of America (Journal of the Sociology and Theory of Religion, 2019)
For the study we leave the key issue – How is that hispanics immigrants have found help in the churches of federal triangle Washington DC and Maryland and Virginia in the face of the migration policies of religious persecution advocated by the Unite States of America? We define as a aims to verify that the churches are a space of shelter and support to immigrants, to analyze if the churches are meeting organizations were immigrants reinforce your identity, to understand if have an active role in religious involvement and relationship with the Curch. The methodology is mixed qualitative/quantitative nature, supported by statistical, inteviews and questionaries, and it was a probability and intentional sample. Data analysis made possible to conclued that beyond the crisis of globalization, and the revival of identity debate, instead of rethinking the american idiosyncrasy according to the founding principles based in the liberty, equality and ethnic and cultural plurality, its postmodern deconstruction has been fostered, giving rise to paradoxical situations of migratory and religious persecution.
Keywords: migration, religious persecution, hispanics, sanctuary.